2020
DOI: 10.5194/bg-17-6527-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of eddy-related deep-ocean current variability in the northeast tropical Pacific Ocean induced by remote gap winds

Abstract: Abstract. There has been a steady increase in interest in mining of deep-sea minerals in the Clarion–Clipperton Zone (CCZ) in the eastern Pacific Ocean during the last decade. This region is known to be one of the most eddy-rich regions in the world ocean. Typically, mesoscale eddies are generated by intense wind bursts channeled through gaps in the Sierra Madre mountains in Central America. Here, we use a combination of satellite and in situ observations to evaluate the relationship between deep-sea current v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
(84 reference statements)
2
16
0
Order By: Relevance
“…The centre of the eddy at the sea surface passed the area at the beginning of May (Purkiani et al, in review). According to Purkiani et al (2020), the effect of the eddy at the seafloor in ~4 km depth would be expected 2 to 4 weeks later, which in our case would mean a date when our sensors had already been recovered from the seafloor. Even so, a model simulation by Purkiani et al (in review), shows that the effect of this specific eddy most likely only reached down to 1500 m water depth.…”
Section: Sediment Mobilisation and Dispersion Of The Plumementioning
confidence: 81%
See 1 more Smart Citation
“…The centre of the eddy at the sea surface passed the area at the beginning of May (Purkiani et al, in review). According to Purkiani et al (2020), the effect of the eddy at the seafloor in ~4 km depth would be expected 2 to 4 weeks later, which in our case would mean a date when our sensors had already been recovered from the seafloor. Even so, a model simulation by Purkiani et al (in review), shows that the effect of this specific eddy most likely only reached down to 1500 m water depth.…”
Section: Sediment Mobilisation and Dispersion Of The Plumementioning
confidence: 81%
“…However, during the passage of mesoscale eddies, which have their clearest expression at the ocean surface but of which the effect occasionally extends to the seafloor at >4 km depth, average current speeds increase to ~8 cm s -1 , with peak values of up to 24 cm s -1 (Aleynik et al, 2017). Whilst background bottom currents are probably not strong enough to resuspend surface sediment most of the time, resuspension might well occur under peak bottom currents associated with these mesoscale eddies (Purkiani et al, 2020). Direct observations of (Martıńez Arbizu and Haeckel, 2015;Peukert et al, 2018) and SO268 (Gazis, 2020;Haeckel and Linke, 2021).…”
Section: Working Areamentioning
confidence: 99%
“…Among the identified long-lived eddies, the one which was anticipated to most likely pass through the location of the German exploration contract area (eastern CCZ) was selected. A previous study in this area (Purkiani et al, 2020) shows that most of the long-lived ACEs in the NETP converge to a meridional corridor between 10 and 12 • N. In that study, an automated EDA developed by Nencioli et al ( 2010) was applied and tested on the long-term sea level anomaly (SLA) data to identify and characterize the mesoscale eddies in this region. To forecast the eddy center positions, a simple prediction method based on the average eddy position within the 7 d prior to the desired day was performed as follows:…”
Section: Satellite Data and Eddy Detection Processmentioning
confidence: 99%
“…Due to recent advances in the development of eddy detection algorithms (EDAs) and the widespread availability of satellite altimeter data, our knowledge on eddies and their surface characteristics has improved significantly (e.g., Chelton et al, 1998Chelton et al, , 2000Chaigneau and Pizarro, 2005;Chaigneau et al, 2008;Liang et al, 2009). Applying an EDA to 24 years of altimeter data (Purkiani et al, 2020), it has been shown that between four and six long-lived (lifetime > 90 d) anticyclonic eddies (ACEs) are generated in the NETP annually, mostly initiated off the west coast of Mexico by the Tehuantepec (TT) and Papagayo (PP) gap winds, which can travel distances greater than 1000 km westwards into the open ocean. The analysis of these long-lived eddies shows that they spread in a narrow meridional corridor between 10 and 12 • N in the interior of the ocean, taking 5-6 months to reach the designated region for future deep-sea mining in the eastern CCZ.…”
Section: Introductionmentioning
confidence: 99%
“…The most in-depth information is related with prototype FN collector tests in German and Belgian contract areas in CCZ [82,84]. Some basic studies in and around the areas [85,86], and numerical simulation studies of sediment plume [87,88] were reported on the basis of some baseline cruises. The prototype collector test and large-scale impact experiment finished in 2021 [89].…”
Section: Large-scale Deep-sea Impact Experiments Scheduled and Simulation Studiesmentioning
confidence: 99%